(3QSGdI aj RjGQI bHQ GdQShd Ydjg GdUdGI hGdSdGes
(3ChdgG (B:s
(3bHQi hLHJ dg TaGYJi jhe GdbjGeg heG ef CMO ef CeJi s
(3BNQgG (B:s
(3GHfG GdgOjI jQbU s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3GdMOjK h GdeUWdMs